Ways to cope with interpersonal emotional barriers in academic volleyball teams - Cherepov, E. A.; Kalugina, G. K. (Theory and Practice of Physical Culture, 2017)
The study considers problems of interpersonal emotional barriers in the academic volleyball teams that may trigger conflicts and disagreements - largely due to the players being unskilful and ineffective in communication domain. Subject to the study were 30 players aged 18-23 years from two picked volleyball teams (women`s and men`s) of South Ural State University. The emotional control domain of the players was classified into the following five elements for analysis: poor emotional control ability; excessive emotionality; inflexible and underdeveloped emotionality; dominance of negative emotions; and unwillingness to make friends using the emotional toolkit. To help the players overcome the interpersonal emotional barriers, we developed a communication skills improvement training including role playing games and special exercises to develop the individual communication control knowledge and skills [1]. In the role playing games the players were encouraged to report and analyse their own (and teammates`) actions, feelings, thoughts and sensations to better understand the behavioural models of the surrounding people.